The Mediating Role of Corporate Social Responsibility Disclosure on Cash Holding: Evidence from Basic Industry and Chemical Companies in Indonesia - Arfianti, Elsa; Arfan, Muhammad; Yusmita, Fifi (Universitas Syiah Kuala, 2023)
Objective This study aims to examines the role of corporate social responsibility (CSR) disclosure in mediating the influence of financial leverage, profitability, and ownership of institutional on cash holding.Design/Methodology The population of this study consists of 203 observations in basic industry and chemical companies listed on the Indonesia Stock Exchange from 2015 to 2020. This study utilizes secondary data obtained from annual report, and the data is subsequently analyzed using path analysis.Results According to the findings of this study, financial leverage and profitability have a negative effect on CSR disclosure, whereas institutional ownership has a positive impact. Financial leverage reduces cash holding, but profitability, institutional ownership, and CSR disclosure increase cash holding. CSR disclosure mediates the financial leverage and institutional ownership effects on cash holding. It does not, however, as mediating effect of profitability on cash holding.Research limitations/implications Because the researchers only looked at basic industry and chemical companies on the IDX, the results cannot be applied to all companies on the IDX. The findings of this research have implications for the importance of efficiently managing cash holding by paying attention to the factors that influence them, which include financial leverage, profitability, institutional ownership, and CSR disclosure.Novelty/Originality CSR disclosure is used in this study to mediate the financial leverage, profitability, and ownership of institutional effects on cash holding. It is analyzed using path analysis, which has never been used in previous studies. In addition, this study used a relatively long period with a larger number of observations.